The Installation of Closed Circuit Television Cameras to Prevent Increasing Rate of Crime in Barangay Commonwealth Quezon City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on installing Closed Circuit Television Cameras to prevent the increasing crime rate in Barangay Commonwealth, Quezon City. Two groups from Barangay officials and the Philippine National Police were selected using purposive sampling based on their knowledge and skills regarding the information desired. The study employed a Quantitative research design. Specifically, the purposive sampling technique, questionnaire with close-ended questions, procedure of data gatherings, collection of material and statistical treatment of the data were used to the effectiveness of the installation of Closed Circuit Television Cameras to prevent an increasing rate of crime in Barangay Commonwealth, Quezon City. The researcher interviewed the Barangay officials and police officers. The main instrument used to gather information is to answer the specific problem raised in every question included in the questionnaires. In this method, the written respondent is to reply as objectively and honestly as possible. Questions were translated into Tagalog to ensure the validity of the responses, that is, correct interpretation and understanding by the respondents of the specific item in line with the purpose of the study. The study concluded that based on the demographic profile of the two groups of respondents’ Barangay officials and police officers in Barangay Commonwealth, Quezon City, the majority of the respondents came from the age bracket 18 - 25 years old, male, single and degree holders. In the assessment, the police officers and Barangay officials know the effectiveness of installing CCTV cameras. As assessed, the Barangay officials and police officers effectively install CCTV cameras to prevent property crime, infractions and crimes against persons. The study revealed that installing Closed Circuit Television Cameras can help the Barangay officials and PNP prevent increasing crime rates. However, Closed Circuit Television Cameras can enhance the monitoring and the safety of the area better than the CCTV area. The study recommended that the Closed Circuit Television Cameras be used to enhance the area's safety to improve continuously.